Development of dynamic and comparative functions of estimation of innovative potential - Kosenko, Oleksandra (University of Miskolc, 2010)
Questions of the rate fixing of different indexes of work of industrial enterprises are considered in the article. Special attention is paid to indexes which form the separate constituents of the innovative potential of machine manufacturing enterprises. The author offers two different approaches to the setting of norms for indexes of work in enterprises, the use of which will have a considerable economic effect in practice.